Molecularly imprinted polymers for illicit drug detection: A review of computational and synthesis methods - Neres, Lariel Chagas da Silva [UNESP]; Khan, Sabir; Zeb, Shakeel; Sotomayor, Maria Del Pilar Taboada [UNESP]; Calvo-Marzal, Percy (Elsevier, 2025)
This review discusses the current state of molecularly imprinted polymers (MIPs) used for drug extraction and quantification. It begins with an introduction to MIP synthesis techniques that utilize illegal drugs as templates. The subsequent sections explore applications, focusing on the detection of illegal narcotics. The advantages and limitations of MIPs receive detailed examination. A comprehensive literature survey then covers various classes of illicit drugs, including opioids, stimulants, cannabinoids, and hallucinogens. Notably, the review highlights the role of computational simulations, including density functional theory (DFT), in optimizing MIP fabrication and enhancing performance. The review concludes with a discussion on the challenges related to the lack of standard parameters for selectivity, the need for robust characterization methods, and the pros and cons of using nanomaterials in MIPs. Recommendations for resolving these issues and potential future developments aimed at broadening the application scope in relevant fields are presented. Overall, this review serves as a valuable resource for researchers involved in the development and application of illicit drug detection technologies using molecularly imprinted polymers.